2019
DOI: 10.1111/jvim.15487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the foal survival score in a Danish‐Swedish population of neonatal foals upon hospital admission

Abstract: Background It is highly desirable to assess the probability of survival in sick neonatal foals upon admission. The foal survival score (FSS) is a published scoring system used to estimate the probability of survival in hospitalized neonatal foals <4 days old. Hypothesis/Objectives To evaluate the ability of the FSS to predict survival in older foals from a geographically different area compared to the original study. Animals Five‐hundred nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…One of the limitations of the current study is that the results of the CIG were not compared with the results obtained using a clinical pathology laboratory (online supplementary figure 1). Given the potential applications of CIG in equine neonatology and endocrinology, it was not considered as a problem as, in clinical practice, most therapeutic decisions are made based on POC results rather than on clinical pathology laboratory results 27 28. Another limitation of the study is that sensors were not investigated in regard to their marketed longevity of up to a 14-day wearing time.…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of the current study is that the results of the CIG were not compared with the results obtained using a clinical pathology laboratory (online supplementary figure 1). Given the potential applications of CIG in equine neonatology and endocrinology, it was not considered as a problem as, in clinical practice, most therapeutic decisions are made based on POC results rather than on clinical pathology laboratory results 27 28. Another limitation of the study is that sensors were not investigated in regard to their marketed longevity of up to a 14-day wearing time.…”
Section: Discussionmentioning
confidence: 99%
“…6 The score has been validated under Scandinavian circumstances and with slightly older foals (until 14 days of age) than the original American sample and found to perform reasonably well. 26 A high survival score indicates a high chance for survival.…”
Section: Survival Scorementioning
confidence: 99%
“…Previous studies have suggested that specific cardiovascular indices, hematological and serum biochemical variables (eg, leukocyte and neutrophil count, venous and arterial blood gas analysis, lactate, anion gap), as well as selected physical examination parameters upon presentation (eg, hypothermia, tachypnea, and ability to stand) are significantly associated with outcome of critical illness in foals 6–8 . Additionally, the use of survival scores has been established in both human and equine ICUs to predict outcome, estimate the severity of disease, and to facilitate evaluation of treatment interventions 9,10 . A simple equine neonatal scoring system (foal survival score) may aid in early determination of prognosis for survival, based on a reported sensitivity of 78 10 and 96%, 11 and specificity of 58 and 71%, in 2 recent studies at separate locations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of survival scores has been established in both human and equine ICUs to predict outcome, estimate the severity of disease, and to facilitate evaluation of treatment interventions 9,10 . A simple equine neonatal scoring system (foal survival score) may aid in early determination of prognosis for survival, based on a reported sensitivity of 78 10 and 96%, 11 and specificity of 58 and 71%, in 2 recent studies at separate locations. The foal survival score is based on easily obtainable clinical variables, including prematurity, cold extremities, presence of > 2 infectious or inflammatory sites, blood glucose concentration, total WBC count, and immunoglobulin G concentrations, which can be assessed on admission.…”
Section: Introductionmentioning
confidence: 99%